Sweetness & lightning. 3 - Amagakure, Gido (Kodansha Comics, an imprint of Kodansha USA Publishing, LLC, 2016)
"The unlikely trio of Kohei, Kotori, and Tsumugi continue their cooking camaraderie-- but there are new challenges on the horizon, both culinary and otherwise. It's exam season, which is stressful for both Kohei the teacher and Kotori, his student. Then, Kohei gets sick, and Tsumugi's a little too determined to take care of her dad. And there's a big change coming in Kotori's life, which might put an end to the trio's kitchen time for good..."--Back cover.